Strategi Pengembangan Manajemen Risiko pada Perguruan Tinggi Swasta Islam di Indonesia dengan COSO Framework - Aan Nurhasanah; Yono Haryono (IRTIQO' : Postgraduate Journal of Islamic Economics, Finance and Accounting Studies, 2024)
Risk is a necessity for all organizations, including private Islamic universities in Indonesia. The implementation of integrated risk management is an important step for Islamic private universities in Indonesia to achieve their goals and contribute to the progress of the nation. The purpose of this study is to design the development of risk management strategies for private Islamic universities through the application of the COSO framework. This research uses qualitative methods through model development and weighting using the Delphi-ANP (Analytic Network Process) method, involving 10 respondents from regulators, experts and practitioners. The results of this study show that there is a mixed level of agreement among experts regarding the risks faced by private Islamic universities. Management is the top priority in risk management, followed by governance, finance and technology. Based on the order of priority, the right strategy in developing risk management in private Islamic universities through the COSO framework, the Control Environment element is the most important. ANP results that show management as the top priority are in line with COSO principles that emphasize the importance of management's role in managing risk. The application of COSO can assist universities in developing a more structured and systematic strategy to manage risk.